Perbandingan Berat Molekul Protein Total Tanaman Selada (Lactuca sativa L.) Hasil Plant Factory dan Ditanam di Tanah Menggunakan SDS-PAGE - Rizki, Muhamad Farrel; Wirawan, I Gede Putu; Suada, I Ketut (Agrotrop : Journal on Agriculture Science; Vol 14 No 2 (2024), 2024)
Comparison of Total Protein Molecular Weight of Lettuce (Lactuca Sativa L.) Plant Factory and Planted in the Ground Using SDS-PAGE. Lettuce ( Lactuca sativa L.) is a plant that contains nutrients and protein that are good for human needs. Lettuce is often found in Indonesian agriculture because lettuce has growing conditions that are very suitable for the Indonesian climate. The purpose of this study was to determine the comparison of protein profiles of lettuce plants grown on the ground with those grown using the hydroponic plant factory system. This research was conducted from May to June 2023 at the Laboratory of PT Genetika Science Indonesia, Tangerang City. This research stage consists of sampling, protein extraction, electrophoresis, and data analysis. Comparisons were made by comparing the two sample data that had been carried out by electrophoresis by looking at the molecular weights of each sample. Plants grown in the soil had higher molecular weights than those grown in the plant factory and each had 12 different proteins. Both samples produced two other same protein bands of 69.65 kDa and 11.97 kDa.